2022
DOI: 10.1155/2022/1946104
|View full text |Cite
|
Sign up to set email alerts
|

Sequential and Dynamic Variations of IL-6, CD18, ICAM, TNF-α, and Microstructure in the Early Stage of Diabetic Retinopathy

Abstract: Objective. The purpose of this project is to make sequential and indepth observation of the variations of retinal microvascular, microstructure, and inflammatory mediators at the early stage of diabetic retinopathy (DR) in streptozotocin-induced diabetes mellitus (DM) rats. Methods. DM was induced by a single intraperitoneal injection of 60 mg/kg body weight streptozotocin (STZ). The fluorescein fundus angiography, hematoxylin and eosin staining, periodic acid-Schiff staining, fluorescence imaging techniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Thus, VEGF-related mechanisms may be characteristic for more advanced DR. This supposition is further supported by Shi et al and Xiao et al, who found that retinal vessel permeability was significantly increased only after the eighth week of diabetes [55,56]. Furthermore, upon histopathological examination of the retina, a characteristic of early DR was noticed, neural degeneration [57].…”
Section: Discussionmentioning
confidence: 59%
“…Thus, VEGF-related mechanisms may be characteristic for more advanced DR. This supposition is further supported by Shi et al and Xiao et al, who found that retinal vessel permeability was significantly increased only after the eighth week of diabetes [55,56]. Furthermore, upon histopathological examination of the retina, a characteristic of early DR was noticed, neural degeneration [57].…”
Section: Discussionmentioning
confidence: 59%
“…For TNF-α, study indicated that the expression of TNF-α mRNA was significantly increased in diabetic rats induced by a single intraperitoneal injection of 60 mg/kg STZ, and Adeno-associated virus (AAV)-mediated expression of human TNF-α in the murine eye induces retinal inflammation 54 . More importantly, TNF-α released from the activated microglia induced BRB damage, which in turn leaded to inflammation of the retinal 55 .…”
Section: Constructionmentioning
confidence: 99%
“…While BCVA did improve with the use of ranibizumab, addition of DHA to these regimens led to an increase in the total antioxidant capacity (TAC) and to a larger reduction in the level of inflammatory cytokines, particularly IL-6. The reduction in IL-6 level is notable because there is evidence that pathways mediated by this cytokine are linked to vascular degenerative changes within the retina of patients with DR [44]. Furthermore, in terms of the clinical outcomes, a greater improvement of membrane thickness in patients with macular edema was observed with supplementary use of DHA-containing nutraceutical supplements, in addition to ranibizumab [43].…”
Section: Omega-3 Fatty Acids and Their Therapeutic Usesmentioning
confidence: 99%